670 DEXMEDETOMIDINE SEDATION FOR PULMONARY VEIN ISOLATION PROCEDURE. (15th December 2022) - Sorrentino, Sergio; Sanniti, Aurora; Zagari, Domenico; Renzullo, Elvira; Spadacini, Giammario; Moretti, Paolo; Tritto, Massimo
Abstract: Background: Peri-procedural anesthesia for catheter ablation of atrial fibrillation (AF) varies from conscious sedation to general anesthesia. Current guidelines do not suggest any specific strategy, thus the choice between different protocols is mainly driven by local expertise, operator and/or patient preference and availability of a dedicated anesthesiology team. Propofol is often the drug of choice despite the risk of respiratory depression. Few data have recently reported operator-directed nurse-administered dexmedetomidine (DEX) sedation as an effective and safe strategy. Aim of the study: To evaluate the outcomes of operator-directed nurse-administered DEX sedation in AF ablation (pulmonary vein isolation-PVI). Method: Between May 2022 and August 2022, 41 consecutive patients (male 83%, median age 64 years, IQR 57-71) with drug-refractory paroxysmal (n.27;66%) or persistent AF (n.14;34%) underwent first PVI procedure under DEX sedation. Our sedation protocol consisted of continuous intravenous administration of DEX (0.2–0, 7 µg/kg/hr) titrated throughout the procedure to achieve mild to moderate sedation (Modified Observer's Assessment of Alertness and Sedation Scale 2-3). A single dose of Ondansetron (4 mg) was administered in the beginning of procedure. Adjunctive doses of fentanyl (cumulative dose 50-100 µg) were administered before the beginning of radiofrequency (RF) delivery and in case of inadequate control of the pain. A low dose propofol bolus (<1mg/kg) was eventually added for electrical cardioversion (ECV). Sedation-related complications were evaluated, including sustained hypoxemia (SpO2 <90%), need of anesthesiologist support and persistent hypotension (SBP < 90 mmHg). The day after the procedure, patients' satisfaction and pain (0-100 scale) were assessed by a standardized questionnaire. Results: Pulmonary vein isolation was performed either with Low Power Long Duration (LPLD, n.17;41, 46%) or High-Power Short Duration (HPSD, n.24;58, 54%) RF protocol. Median procedure time was 135' (IQR 110-170'). Median DEX dose was 0, 30 µg/kg/hr (IQR 0, 27-0, 33 µg/kg/hr). Median fentanyl dose was 75 µg (IQR 50-100 µg). In patients needing for ECV (n. 16; 39%), median propofol dose was 60 mg (IQR 47, 5–105 mg). Thirteen patients (31, 7%) had one or more significant risk factor (obesity, severe heart failure, pulmonary comorbidity, coronary artery disease) for anesthesia-related complications. Median pain scale value was 20 (IQR 10-50). Majority of patients (90, 2%, n.37) reported mild to moderate pain (pain <60/100) during the procedure and satisfaction was overall high (median value 90, IQR 80-100), with a 90, 2% of patients declaring a satisfaction of 60/100 or more. These results were independent from baseline characteristics (sex, age, AF type, HF, CAD, pulmonary comorbidity, obesity) and procedural aspects (LPLD vs HPSD, procedure time, need for ECV). A strong linear correlation was found between patients' satisfaction and reported pain (r=-0, 59). Only 1 (2, 4%) sedation-related complication occurred, consisting in sustained post procedural hypotension treated with volume repletion. Conclusions: in our experience, dexmedetomidine (DEX) sedation protocol during catheter ablation of atrial fibrillation is associated to high patients' satisfaction and no respiratory complications. It seems to be also feasible in patients at higher risk for anesthesia-related complications (severe heart failure, BMI > 30 kg/m2), generally excluded from previous studies.